A critical period for faces: Other-race face recognition is improved by childhood but not adult social contact - McKone, Elinor (Sci Rep, 2019)
Poor recognition of other-race faces is ubiquitous around the world. We resolve a longstanding contradiction in the literature concerning whether interracial social contact improves the other-race effect. For the first time, we measure the age at which contact was experienced. Taking advantage of unusual demographics allowing dissociation of childhood from adult contact, results show sufficient childhood contact eliminated poor other-race recognition altogether (confirming inter-country adoption studies). Critically, however, the developmental window for easy acquisition of other-race faces closed by approximately 12 years of age and social contact as an adult — even over several years and involving many other-race friends — produced no improvement. Theoretically, this pattern of developmental change in plasticity mirrors that found in language, suggesting a shared origin grounded in the functional importance of both skills to social communication. Practically, results imply that, where parents wish to ensure their offspring develop the perceptual skills needed to recognise other-race people easily, childhood experience should be encouraged: just as an English-speaking person who moves to France as a child (but not an adult) can easily become a native speaker of French, we can easily become “native recognisers” of other-race faces via natural social exposure obtained in childhood, but not later.